Conceptualizing legitimacy: What to learn from the controversies related to an “essentially contested concept” - Wiesner, Claudia; Harfst, Philipp (Frontiers in Political Science, 2022)
Based on a genealogy of the concept of Legitimacy, the goal of the paper is to develop a proposal that unites normative-theoretical and empirical approaches and hence reconciles two different conceptual-theoretical camps in legitimacy research. Legitimacy is a core concept in Political Science that relates to fundamental questions of politics, polity and policy–the relation between rulers and ruled, the properties of a political system, its democratic quality, the rule of law, and its policy output. However, in academia, no consensus has evolved on the conceptual and empirical core of legitimacy, it is still essentially contested. One main reason for this is that a concept such as legitimacy is not only a tool for analysis, but can also become an object of academic controversy itself, as researchers give different answers to key questions related to conceptualizing it. This is why academic controversies on a concept highlight key issues, questions and dimensions of understanding, defining, and operationalising it—which is also the case for legitimacy. The paper therefore recollects the main controversies around the concept of legitimacy since the 1950's by tracing a genealogy of legitimacy in the Social Sciences. A genealogy is a methodological tool in intellectual and conceptual history. Different from a classical literature review, a genealogy summarizes the main lines and traditions of thinking on a concept, the key controversies, predominant understandings, and crucial issues of conceptualizing it. In the conceptual debates on legitimacy in Political Science, the core controversy is the one between normative-theoretical and empirical approaches. Based on the genealogy, we develop a proposal for conceptualizing legitimacy that enables to reconcile the normative-theoretical and empirical camps in legitimacy research.